Evaluation of the behavioral performance of a text mining algorithm on internet connections in the municipalities of Conceição do Araguaia and Redentação - PA (Research, Society and Development, 2023)
The general objective of this study was to evaluate the behavioral performance of a text mining method written in Python with attributes aimed at Bayesian networks in low-speed connections in the cities of Conceição do Araguaia and Redenção-PA located in the interior of the state of Pará. Among the authors researched for the conceptual constitution of this work, Caminha et al (2017), Conte et al (2016), Santana et al (2016), Almeida et al (2016) and Mata et al (2013) stand out. The methodology used is found (Caminha et al, 2017), which, in turn, is classified as qualitative-analytical, as it seeks to work on deepening the evaluation of behavioral performance based on texts mined from the social network twitter. The most relevant conclusions of this work resulted from the comparison of the results obtained in the city of Conceição do Araguaia and Redenção, where it was possible to observe nonconformities in the performance of data traffic in both cities, both for positive and negative aspects despite the equality in speed. of the link in both cities in the years 2016, 2017, 2021 and 2022, in order to compare the existence of an evolution in its behavior.